2016
DOI: 10.1080/15412555.2016.1260539
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic and Neutrophilic Airway Inflammation in the Phenotyping of Mild-to-Moderate Asthma and Chronic Obstructive Pulmonary Disease

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are heterogeneous diseases with different inflammatory phenotypes. Various inflammatory mediators play a role in these diseases. The aim of this study was to analyze the neutrophilic and eosinophilic airway and systemic inflammation as the phenotypic characterization of patients with asthma and COPD. Twenty-four patients with asthma and 33 patients with COPD were enrolled in the study. All the patients were in mild-to-moderate stage of disease, and none o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…This study captured clusters based on breathomics that were not predominantly driven by diagnosis but were instead driven by clinical/inflammatory characteristics. Most of these driving factors are commonly identified when attempting to phenotype asthma and/or COPD patients [25][26][27][28][29][30]. Cluster 1 found in our study contains predominantly females with a high BMI, no inflammation and high symptom scores.…”
Section: Discussionmentioning
confidence: 70%
“…This study captured clusters based on breathomics that were not predominantly driven by diagnosis but were instead driven by clinical/inflammatory characteristics. Most of these driving factors are commonly identified when attempting to phenotype asthma and/or COPD patients [25][26][27][28][29][30]. Cluster 1 found in our study contains predominantly females with a high BMI, no inflammation and high symptom scores.…”
Section: Discussionmentioning
confidence: 70%
“…A significant correlation was found between number of sputum eosinophils (A phenotype) and the type of dyspnea group (D phenotype) (0.535; P ≤ .001). Percentage sputum eosinophil count was predictive of dyspnea (D phenotype) COPD with AUC of 0.831 (95% CI 0.77–0.89; P ≤ .001) (Figure A), and in some studies, the correlation has been close …”
Section: Discussionmentioning
confidence: 89%
“…These can be further divided according to the form of pollutant: gaseous pollutants, liquid pollutants, and solid pollutants; and according to the nature of the pollutant: chemical contaminants, physical pollutants, and biological contaminants . The harm of environmental pollutants to the human body is mainly reflected in respiratory mucosa damage and obstructive pulmonary disease because the respiratory tract is the first thing affected by environmental exposure . Several studies have shown that in environments with air pollution, the cilia in the human respiratory tract become shorter or are missing, which affects their ability to clear the respiratory tract.…”
Section: Environmental Pollutantsmentioning
confidence: 99%
“…39 The harm of environmental pollutants to the human body is mainly reflected in respiratory mucosa damage and obstructive pulmonary disease because the respiratory tract is the first thing affected by environmental exposure. 40 Several studies have shown that in environments with air pollution, the cilia in the human respiratory tract become shorter or are missing, which affects their ability to clear the respiratory tract. For example, when experimental animals were exposed to higher concentrations of ozone (4 ppm), it was observed that the vesicles of the ciliated membrane and the structure of the tracheal cilia were damaged.…”
Section: Environmental Pollutantsmentioning
confidence: 99%